EFFECT OF DIFFERENT TREATMENT PROTOCOLS ON THE SERUM BIOCHEMICAL PARAMETERS OF FOLLICULAR CYST AFFECTED COWS - K. Ragul; N. Arunmozhi; S. Satheshkumar; S. Murugavel; S. Raja; S. Prakash; P. Jayaganthan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Follicle like structures with a minimum of 17 mm diameter and persisting for more than 6 days in the absence of corpus luteum is called as follicular cyst. It is the hypothalamo-hypophyseo gonadal axis that governs the reproductive events primarily. Plasma is a medium that reflects the changes in any organ apart from providing nutrients and draining the metabolic wastes. Cows brought for infertility treatment were screened and cows which were diagnosed as follicular cyst randomly allotted in to four groups of eight cows each. Different groups were subjected to different treatment protocols viz, Regular co-synch protocol, modified co-synch protocol, Trans-gluteal follicular cyst evacuation technique and trans-gluteal follicular cyst evacuation technique cum modified co-synch protocol for Group I, II, III and IV, respectively. Blood samples were collected from all the cows of different groups on day 0 (initiation of treatment), 7 and 9 of treatment and were analyzed for biochemical parameters. Cholesterol, triglyceride, total protein, calcium and phosphorus concentration was quantified using an automatic analyser UV-VIS spectrophotometer. There was no significant difference (P > 0.05) noticed between the mean concentration of biochemical parameters of different treatment groups, on days 0 and 7 in serum. The mean concentrations of cholesterol were 116.13±20.28, 59.67±10.50, 70.88±6.57 and 64.00±8.36 mg/dl in Group I, II, III and IV cows, respectively and were significantly (P < 0.05) higher in Group I. The mean concentration of all other biochemical parameters were non-significant (P > 0.05) between all treatment groups, on day 9 in serum. This might be due to steroid bio transformation of cholesterol.